2017
DOI: 10.1371/journal.pone.0179978
|View full text |Cite
|
Sign up to set email alerts
|

Differential effects of heat shock protein 90 and serine 1179 phosphorylation on endothelial nitric oxide synthase activity and on its cofactors

Abstract: Endothelial nitric oxide synthase (eNOS) is responsible for maintaining systemic blood pressure, vascular remodeling and angiogenesis. Previous studies showed that bovine eNOS serine 1179 (Serine 1177 for human eNOS) phosphorylation enhanced NO synthesis. Meanwhile, heat shock protein 90 (Hsp90) plays a critical role in maintenance of eNOS structure and function. However, the regulatory difference and importance between Serine 1179 phosphorylation and Hsp90 on eNOS activity have not been evaluated. In current … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 27 publications
0
17
0
Order By: Relevance
“…Moreover, inhibition of Hsp90 or silencing of Hsp90 causes the eNOS dimer to dissociate into monomers and exposes Ser1179 and Thr497 on the monomers to various phosphatases, resulting in eNOS dephosphorylation and degradation. Structure studies showed that Hsp90 associates with the oxygenase domain of eNOS in which eNOS also associates with many kinds of different cofactors or substrates, such as Heme, tetrahydrobiopterin (BH4), and L-arginine (Balligand, 2002;Chen et al, 2017). In fact, Hsp90 uniquely regulates eNOS through specifically changing a few eNOS cofactor affinity, such as reduced nicotinamide adenine nucleotide phosphate and calcium (Ca 2+ )/calmodulin (Chen et al, 2017).…”
Section: Heat Shock Protein 90 and Amp-activated Protein Kinasementioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, inhibition of Hsp90 or silencing of Hsp90 causes the eNOS dimer to dissociate into monomers and exposes Ser1179 and Thr497 on the monomers to various phosphatases, resulting in eNOS dephosphorylation and degradation. Structure studies showed that Hsp90 associates with the oxygenase domain of eNOS in which eNOS also associates with many kinds of different cofactors or substrates, such as Heme, tetrahydrobiopterin (BH4), and L-arginine (Balligand, 2002;Chen et al, 2017). In fact, Hsp90 uniquely regulates eNOS through specifically changing a few eNOS cofactor affinity, such as reduced nicotinamide adenine nucleotide phosphate and calcium (Ca 2+ )/calmodulin (Chen et al, 2017).…”
Section: Heat Shock Protein 90 and Amp-activated Protein Kinasementioning
confidence: 99%
“…Structure studies showed that Hsp90 associates with the oxygenase domain of eNOS in which eNOS also associates with many kinds of different cofactors or substrates, such as Heme, tetrahydrobiopterin (BH4), and L-arginine (Balligand, 2002;Chen et al, 2017). In fact, Hsp90 uniquely regulates eNOS through specifically changing a few eNOS cofactor affinity, such as reduced nicotinamide adenine nucleotide phosphate and calcium (Ca 2+ )/calmodulin (Chen et al, 2017). Meanwhile, sufficient study data confirm that mitochondrial dysfunction in pulmonary arterial endothelial cells (PAECs) decreases the cellular ATP levels and Hsp90 chaperone activity, resulting in a reduced interaction between Hsp90 and eNOS in cardiovascular disorders (Sud et al, 2008).…”
Section: Heat Shock Protein 90 and Amp-activated Protein Kinasementioning
confidence: 99%
“…eNOS activation is mainly calcium dependent, but some studies have shown that a calcium independent pathway exists, via heat shock protein 90 (HSP90). HSP90 is also known to localize to cilia axonemes, and may act as a signal transductor that interacts with eNOS in the vasculature [62,63]. HSP90 activation can lead to an increase in eNOS activity while calcium levels are high, and can also lead to more eNOS activity at low calcium levels due to its ability to directly bind to eNOS and increase the binding affinity for calmodulin [64,65].…”
Section: Vasodilationmentioning
confidence: 99%
“…Though eNOS triggering is principally a Ca 2+ -dependent process, some studies have suggested a Ca 2+ -independent pathway in NO biosynthesis is also possible. This Ca 2+ -independent pathway depends on the heat shock protein 90 (HSP90) [129,130]. HSP90 is a molecular chaperone, but it may also act as a signal transduction agent concomitant with eNOS in several systems, including the cardiovascular system.…”
Section: Role Of Primary Cilia In Biochemical Signaling and Hypertmentioning
confidence: 99%